Right ventricular function during left heart bypass evaluated by two-dimensional echocardiography - MIYAMURA, K.; YADA, I.; IMURA, M.; SAITO, K.; WEI, C. M.; HATTORI, R.; OKABE, M.; FUKUYAMA, M.; KUSAGAWA, M.; YUASA, H. (Jinko Zoki, 1985)
Right ventricular (RV) functions during left heart bypass using centrifugal pump were studied in fourteen mongrel dogs They were devided to two groups of normal heart and failing heart RV functions were evaluated hemodynamically and by twodimensional echocardiography (2D-Echo). Incremental increases in LHB flow ratio (LHB flow×100/LHB flow+ascending aortic flow) to 25%, 50%, 75% and maximum flow (about 85-100%) were associated with decrements in interventricular septum (IVS) segmental shortening fraction (SSF) from 54±12% in control, to 43±5%, 42±2%, 35±7% and 0%, respectively. Increasing LHB ratios resulted in decreasing LVED volume and concomitant increased RVED volume decreasing heart rate; increasing RV stroke volume and RV stroke work. When LHB ratio increased from 75% to maximum, the significant reduction in RV ejection fraction (cross sectional area by 2D-Echo) and completely decompressed LV were observed. And also the cross sectional echocardiographic image revealed profoumdly depressed SSF of IVS and RV free wall nearby. Decompressed LV by LHB with maximum flow seemed to decrease the LV wall motion including IVS, that caused to reduce the efficiency of RV contraction Therefor 75% bypass ratio during left heart bypass is more than maximum flow ratio with LV decompression.